2019
DOI: 10.1115/1.4044423
|View full text |Cite
|
Sign up to set email alerts
|

Water Hammer Causes Water Main Breaks

Abstract: Most underground water main breaks can be stopped, since the technology is now available to evaluate water system piping failures and determine corrective actions. The problem is defined in terms of several variables: (1) Water hammer is the initiator of nearly all underground water main breaks. (2) In nonacidic soils, fatigue directly causes piping cracks. (3) In acidic soils, water hammer cracks the pipes, and crevice corrosion is accelerated at those crack sites. Additionally, those cracks serve as moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Additionally, this author disagrees with other proposed causes of water main breaks [15]. Although the cited causes of soil stresses and corrosion are contributing causes to water main breaks, water hammer is the common cause as proven in publications [3,4,7], which in turn were based on hundreds of other references and many years of research. For example, ground shift due to winter temperatures was cited as a cause of piping cracks due to soil stresses, but this author contends that the possibility approaches zero to crack an underground metal pipe when concrete roads above that pipe do no crack.…”
Section: Rebuttals To Alternate Water Main Break Theoriesmentioning
confidence: 79%
See 4 more Smart Citations
“…Additionally, this author disagrees with other proposed causes of water main breaks [15]. Although the cited causes of soil stresses and corrosion are contributing causes to water main breaks, water hammer is the common cause as proven in publications [3,4,7], which in turn were based on hundreds of other references and many years of research. For example, ground shift due to winter temperatures was cited as a cause of piping cracks due to soil stresses, but this author contends that the possibility approaches zero to crack an underground metal pipe when concrete roads above that pipe do no crack.…”
Section: Rebuttals To Alternate Water Main Break Theoriesmentioning
confidence: 79%
“…That is, this simplified approach provides more go-no go conditions to determine if further modeling is recommended. where t 1 =the rise time=0.0021 seconds; ω=the hoop stress frequency of the pipe=7622 Hz (Earlier work showed that this frequency approximation underestimates the frequency for a thick wall pipe, but this error does not significantly influence the maximum DLF for this example); k=the bulk modulus of water=140,000 psi; r=the pipe radius=3.45 inches; T=the ductile iron pipe wall thickness=0.25 inches; g=the gravitational constant=32.174 feet/second 2 ; ν=Poisson's ratio=0.211; ρ pipe =pipe density=0.26 pounds per inch 3 ; ρ water =water density=0.03611 inch 3 ; E=modulus of elasticity=13,400,000 psi; σ static =the thin wall approximation for a hoop stress based on the measured pressure; and σ dynamic =the dynamic stress which is the estimated stress to cause a fatigue failure in the pipe. Since the soil frequency is much lower than the pipe wall frequency, the soil frequency predicts a bounding maximum stress response, and the soil frequency was used for this single degree of freedom approximation to a two degree of freedom system.…”
Section: =mentioning
confidence: 81%
See 3 more Smart Citations